Retractions and Homomorphisms on Some Operations of Graphs. (1st October 2018) - Abu-Saleem, M.
Abstract : The aim of the present article is to introduce and study a new type of operations on graph, namely, edge graph. The relation between the homomorphisms and retractions on edge graphs is deduced. The limit retractions on the edge graphs are presented. Retractions on a finite number of edge graphs are obtained.